The variation of NAD+-SDH gene in mutant white-fleshed loquat - Jing LI; Yong-qing WANG; Dong CHEN; Mei-yan TU; Hong-jiang XIE; Guo-liang JIANG; Jia LIU; Shu-xia SUN (Journal of Integrative Agriculture, 2016)
Loquat (Eriobotrya japonica Lindl.) can be divided into yellow- and white-fleshed cultivars by flesh color. However, a Dongting loquat mutant, which involved bud sport and growing white-fleshed fruit in the central region of the trunk (as wild loquat bears yellow-fleshed fruits naturally), was discovered in the preliminary study. The study cloned the coding sequence (CDS) of NAD+-dependent sorbitol dehydrogenase (NAD+-SDH) gene from the selected materials of mutant loquat, wild loquat and other nine loquat cultivars/accessions, and found that the CDS of NAD+-SDH gene from the mutant loquat, other than the rest two types of materials, had three single nucleotide polymorphisms (SNPs) loci; in addition, the amino acid encoded at variation loci changed accordingly. NAD+-SDH plays an active role in converting sorbitol into fructose in loquat cultivars. For the mutant white-fleshed loquat, the activity of NAD+-SDH rises first and then drops, the sorbitol content decreases steadily, and its fructose content is higher than that in wild loquat from coloration to maturation stage. As demonstrated by the real-time fluorescence quantification PCR analysis, the expression level of NAD+-SDH gene at maturation stage is about 5-fold lower than wild type. It may be assumed that, the three SNPs loci might lead to excessive conversion of sorbitol into fructose under the catalytic action of NAD+-SDH of white-fleshed mutant loquat at maturation stage, resulting in the increase of fructose content and reduced expression abundance of mRNA after transcription. Besides, NAD+-SDH gene may be related to flesh color and carbohydrate variation of white-fleshed mutant loquat.